2021
DOI: 10.1177/14613484211059264
|View full text |Cite
|
Sign up to set email alerts
|

A heuristic review on the homotopy perturbation method for non-conservative oscillators

Abstract: The homotopy perturbation method (HPM) was proposed by Ji-Huan. He was a rising star in analytical methods, and all traditional analytical methods had abdicated their crowns. It is straightforward and effective for many nonlinear problems; it deforms a complex problem into a linear system; however, it is still developing quickly. The method is difficult to deal with non-conservative oscillators, though many modifications have appeared. This review article features its last achievement in the nonlinear vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 100 publications
(129 reference statements)
0
40
0
Order By: Relevance
“…The calculation for the solution (24) being plotted with the numerical solution of the original Equation (1) as shown in Figures 7-9. These figures illustrate the time history of the solution (24) taking into account the relation (29). Investigating these graphs shows the high agreement of the analytical solution with the numerical solution.…”
Section: Numerical Validationmentioning
confidence: 89%
See 4 more Smart Citations
“…The calculation for the solution (24) being plotted with the numerical solution of the original Equation (1) as shown in Figures 7-9. These figures illustrate the time history of the solution (24) taking into account the relation (29). Investigating these graphs shows the high agreement of the analytical solution with the numerical solution.…”
Section: Numerical Validationmentioning
confidence: 89%
“…It was also revealed that the linear damping coefficient plays a dual role in the stability behavior, while the nonlinear counterpart exerted a destabilizing influence on the resonance response. The approximate solution is compared with the numerical solution using the Mathematica software which shows excellent agreements under a specific relation (28) or (29). The effectiveness of the proposed method is also evaluated by the forced Toda model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations